Public deficits and borrowing costs: the missing half of market discipline - Friedrich Heinemann; Viktor Winschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
EMU driven interest rate convergence has led to a significant reduction of borrowing costs for some European governments in the second half of the nineties. The paper deals with the possible consequences for deficit behaviour. Although the impact of interest rates on deficits is a crucial element of the market discipline hypothesis it has widely been neglected in the literature. In the theoretical part, a standard political economic model of budgetary policy (Hettich-Winer) is adapted. It turns out that borrowing costs, measured as the interest-growth-differential, and the level of public debt should be important determinants for public deficits. The econometric part tests these predictions for a panel of OECD countries. The results indicate that there is indeed a significant impact of borrowing costs on the primary surplus. This impact is characterised by a robust asymmetry: Reactions in times of increasing borrowing costs are more pronounced than in times of relaxing conditions.
Keywords: H62; 330; market discipline; borrowing costs; EMU; public debt; government deficits; Öffentlicher Haushalt; Öffentliche Schulden; Kapitalkosten; Realzins; Public Choice; Theorie; OECD-Staaten